Strategic Management of Islamic Boarding School in The Digital Era: Building A Cadre of Leaders who Unit the People at Al Madani Islamic Boarding School Cikalong Majalengka - Mu’min, Amir; Farihin, Farihin; Baskoro, Edi Prio (PT. Anagata Sembagi Education, 2025)
Islamic boarding schools as Islamic educational institutions have a strategic role in producing cadres of leaders who are able to unite the people. In the digital era, the challenges and opportunities for Islamic boarding schools are increasingly complex, so adaptive and innovative strategic management is needed. This study aims to analyze the management strategy of Islamic boarding schools in building a cadre of leaders who unite the people at the Al Madani Cikalong Islamic Boarding School, Majalengka. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that Al Madani Islamic Boarding School implements a digital-based management strategy in education and resource management, including the use of information technology in learning, strengthening the leadership curriculum based on Islamic values, and collaboration with various parties in developing leader cadres. The implementation of this strategy has proven effective in improving the quality of students as prospective leaders who are broad-minded, moderate, and able to adapt to the times